An Evaluation of Flow Shop Sequencing Heuristics - Dannenbring, David G. (Management Science, 1977)
This paper presents computational experience with eleven flow shop sequencing heuristics. Included in the study are three previously unreported heuristics, one of which turns out to be superior to the other ten heuristics tested. The comparisons were made on a variety of problem sizes, up to fifty jobs and fifty operations.